34. TREATMENT RESULTS OF PEDIATRIC PATIENTS WITH PNEUMONIA USING VANCOMYCIN AND SOME RELATED FACTORS AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To review the treatment results of pediatric pneumonia patients using vancomycin andfind out some its related factors.Subjects and methods: Descriptive study of 129 pediatric patients were diagnosed with pneumoniausing treatment vancomycin at the Obstetrics and Pediatrics Hospital from April 2023 to March 2014.Results: The percentage of patients cured and improved after treatment was high, accounted for58.9% and 28.7%, respectively. The death rate was low (1.6%). The median treatment period was 14days. The mean initial maintenance vancomycin dose was 59.5 ± 2.3 mg/kg/day with dosing intervalsevery 8 hours in most pediatric patients in the study (89.9%). The median duration of vancomycintreatment was 10 (7-13) days. The rate of achieving the AUC target (400 - 600 mg.h/L) in the firstdosing was 67.4%. Adverse events during vancomycin infusion accounted for 10.3%. Factorsassociated with an increased risk of subtherapeutic AUC at first measurement include: age > 24months, increased renal clearance, and shock.Conclusion: It is necessary to optimize the initial dose of vancomycin in the population ofpneumonia pediatric patients using vancomycin based on monitoring blood drug concentrationsaccording to AUC taking into account factors such as age, renal clearance, and shock.
Keywords: Pneumonia, vancomycin, trough concentration, area under the curve.